NUTRIENT DIGESTIBILITY AND RUMEN METABOLITE PROFILE CONCENTRATION OF GROWING YANKASA RAMS FED BRACHIARIA MULATO II BASE TOTAL MIXED RATION AT DIFFERENT PERCENT BODY WEIGHT - Ahmed, S. A.; Abdu, S. B.; Amodu, J. T.; Hassan, M. R.; Ishiaku, Y. M.; Salisu, S. G.; Hassan, R.; Sani, R. T. (FUDMA JOURNAL OF SCIENCES, 2022)
Twenty (20) apparently healthy growing Yankasa rams with a mean initial live weight of 20-21kg±0.5kg were used for 120 days feeding and 21 days digestibility trials to was carried out to determine nutrient digestibility and rumen metabolites profile of growing Yankasa rams. The animals were grouped into four with five animals each in a Completely Randomized Design (CRD) and randomly allocated to four treatments. The treatments were 2.5, 3.0, 3.5 and 4.0% body weight. The DM (88.38%), CP (89.70%), NDF (74.54%) and ADF (77.63%) were significantly (P
Keywords: Brachiaria Mulato II; Profile; Digestibility; Yankasa Rams